Changes of Bone Metabolism Markers and Muscular Performance with Combined Aerobic Dance Exercise and Honey Supplementation in Adult Women - Marhasiyah, Rahim; Ooi, Foong Kiew; Wan Zuraida, Wan Abdul Hamid (2016)
OBJECTIVE: This study investigated the effects of combined aerobic dance exercise and honey supplementation on blood bone metabolism markers and muscular power in adult women. METHODS: Forty-four healthy sedentary women (25-40 year-old) were age and weight matched, and subsequently being assigned into four groups with n=11 per group: Control (C), honey supplementation (H), aerobic dance exercise (Ex) and combined aerobic dance exercise with honey supplementation (HEx) groups. Aerobic dance exercise was carried out for one hour per session, three times per week for eight weeks. Blood samples were taken to determine the concentrations of serum total calcium, osteocalcin (bone formation marker), serum C-terminal telopeptide of type 1 collagen (1CTP) (bone resorption marker), and parathyroid hormone (PTH). Meanwhile, subjects’ lower limb muscular power was measured. RESULTS: At the end of 8-weeks of experimental period, serum 1CTP concentration was significant greater in post-test than pre-test in Ex group. The percentage increment in 1CTP was the highest in Ex group. Meanwhile, the percentages of increment in 1CTP and PTH concentrations in HEx group were the lowest compared to the other experimental groups. Regarding muscular performance, Ex and HEx exhibited more discernable beneficial effects on lower limb average power compared to the H and C groups. CONCLUSION: Combination of aerobic dance exercise and honey supplementation has potential to reduce the increment in bone resorption resulting from exercise, and this combination could enhance lower limb muscular power in sedentary women.